Case Report: Serous borderline ovarian tumor and extensive abdominopelvic endometriosis mimicking advanced epithelial ovarian cancer in a postmenopausal patient - Livatova, Katherine; Nguyen, Anthony D.; Pizzuti, John; Lee, Yi-Chun; McEachron, Jennifer (Frontiers in Medicine, 2025)
The lifetime risk of ovarian cancer is 1 in 75, and it is often diagnosed at an advanced stage due to the lack of effective screening. Epithelial ovarian cancer (EOC) is the most common type of ovarian cancer in older patients, with borderline ovarian tumors (BOTs) accounting for 15% of EOC cases. BOTs are usually of low malignant potential. Since platinum-based chemotherapy has not been shown to improve survival rates, cytoreductive surgery (CRS) is recommended as a treatment option. Additionally, endometriosis affects 10.5% of patients with EOC. It often progresses to clear cell and endometrioid ovarian cancer. This progression is believed to result from repetitive cycles of inflammation, mutations in multiple pathways, and microsatellite instability. While other types of cancers, such as BOTs, can arise in cases of endometriosis, they are less common. This case report describes an unusual case of a 62-year-old female patient who appeared to present with advanced-stage epithelial ovarian cancer (EOC) but was unexpectedly diagnosed with a borderline ovarian tumor (BOT) accompanied by extensive endometriosis. The patient’s history of endometriosis, infertility, and low parity increased her risk of developing a BOT; however, her age at presentation was unusual. The key clinical feature of this case that contributes to the existing literature is the vital role of pathology in guiding chemotherapy decisions, particularly when there is disease progression despite ongoing treatment. This highlights the necessity of a thorough history and physical examination, as several aspects in the patient’s medical history were suggestive of a BOT. The patient initially presented with emesis, abdominal distention, postmenopausal bleeding, and a large, rapidly growing pelvic mass, which raised the initial suspicion of advanced EOC. However, she was unable to undergo surgery due to supraventricular tachycardia and venous thromboembolism (VTE) caused by the mass effect of the tumor. Despite being medically unstable, an exploratory laparotomy with resection of the mass was performed. Pathology revealed a stage 1C3 serous BOT within a large endometrioma. Chemotherapy was not required postoperatively. The patient remained under close observation by gynecologic oncology for surveillance, hematology for managing her VTE, and cardiology for monitoring her supraventricular tachycardia (SVT).